Determination of hand grip strength and its correlates during pregnancy: a cross-sectional study - Auwal Abdullahi; Amina Shuaib Bala; Sani Musa Danazumi; Saadatu Maiwada Abubakar; Rislanu Isyaku Adamu; Steven Truijen; Musa Kani Zakari; Christopher Olusanjo Akosile; Wim Saeys; Isa Usman Lawal; Mohammed Etoom; Jibril Mohammed Nuhu; et al. (BMC, 2021)
Abstract Background Pregnancy results in many changes, including reduced hand grip strength (HGS). However, good HGS is required for physical functions such as carrying and breastfeeding the baby after birth. The aim of this study was to determine the factors that may predict HGS during pregnancy. Methods The study was a cross-sectional study approved by the Research Ethics Committees of Kano State Ministry of Health and Aminu Kano Teaching Hospital in Kano, north-west, Nigeria. Pregnant women at the designated hospitals were included in the study if they had no serious comorbidities or any known neurological condition that affects the hands and the neck. Demographic characteristics and independent (predictor) variables (age, weight, height, BMI, maternity leave status, number of full-term deliveries, number of preterm deliveries, number of live births, number of abortuses, gravidity, trimester, systolic blood pressure, diastolic blood pressure, inter arm systolic BP difference [IASBP], inter arm diastolic BP difference [IADBP], and heart rate) of each of the participants were recorded by experienced therapists. The data were analysed using descriptive statistics, t-test, Pearson correlation coefficient and standard multiple regression. Result One hundred and sixty-one pregnant women with mean age, 25.04 ± 4.83 years participated in the study. In the dominant hand, 120 participants (74.5%) had weak grip strength. In the non-dominant hand, 135 participants (83.9%) had weak grip strength. For the dominant hand, the total variance explained by the whole model was significant, 28.5%, F(11, 161) = 1.187, R2 = 0.081, p = 0.300 . In the final model, none of the variables significantly predicted HGS. However, systolic blood pressure contributed to the model more than any other variable (Beta = -0.155). For the non-dominant hand, the total variance explained by the whole model was not significant, 33.1%, F(11, 161) = 1.675, R2 = 0.111, p = 0.089 . In the final model, only systolic blood pressure (Beta = -0.254, p = 0.023) significantly predicted hand grip strength. Conclusion Cardiovascular events or changes during pregnancy (such as change in systolic blood pressure) may be related to HGS in pregnant women. It is therefore, important for clinicians to pay attention to this, in planning rehabilitation strategies for pregnant women.